Analysis of Structure and Diversity of the Kilengwe Forest in the Morogoro Region, Tanzania. (23rd January 2014) - Kacholi, David Sylvester
Abstract : This study investigates the structure, species composition, and diversity of a section of the Kilengwe Forest in Tanzania. In order to accomplish the proposed objectives, 18 plots of 20 m × 20 m were randomly established in the forest and the number of tree species in each plot was identified and counted. The most important families and species were determined using importance value indices at the respective taxonomic levels. Diversity was measured using the Shannon-Wiener and Fisher alpha diversity indices. A total of 276 stems/ha representing 93 species/ha within 26 families were documented from 0.72 ha. Fabaceae and Julbernadia globiflora were the dominant family and species, respectively. Seventy-eight percent of the total species were rare. The average basal area of the forest was 7.1 m 2 /ha. The Shannon-Wiener index (4.02) and Fisher's alpha diversity (35.5) indicated high species diversity within the forest. The species-area and species-abundance curves revealed an escalating trend implying that more sampling efforts could result in a higher number of species existing in the forest. The size class distribution displayed a reverse J-shaped pattern; however, the larger size classes DBH >50 cm were not represented. The study suggests the necessity for anthropogenic disturbance control as this is the major source of forest degradation in the studied area.